Ultrasound features and risk stratification systems to identify medullary thyroid carcinoma. Issue 2 (28th June 2021) - Matrone, Antonio; Gambale, Carla; Biagini, Margherita; Prete, Alessandro; Vitti, Paolo; Elisei, Rossella
Abstract: Objective: Recently, several scientific societies designed ultrasound (US) risk stratification systems (RSS) to guide the workup of thyroid nodules and decide which nodules should undergo fine-needle aspiration cytology (FNAC). However, these systems have been developed against papillary thyroid carcinoma, and scanty data on their role in identifying medullary thyroid carcinoma (MTC) are available. The aims of this study are to describe the US features of MTC and evaluate the performance of RSS in identifying MTC. Methods: Data of 152 consecutive patients with MTC was evaluated. The results of the pre-operative neck US of all patients were collected. Ultrasound features of each MTC were evaluated and classified according to the five main RSS available. Results: Median MTC dimension was 1.3 cm. Most of the nodules showed solid composition, hypoechoic pattern, and regular margins. About half of them showed the presence of calcifications, but only a subgroup had microcalcifications. A minority of the nodules showed a 'taller than wide' shape. Only 7.9% of all MTC showed the simultaneous presence of at least four US features suggestive of malignancy. Ultrasonographic high-risk of malignancy of the MTC included in the five RSS, varied from 45.4 to 47.4%, and performing FNAC was suggested in only 48.7 to 63.8% of all MTC. Conclusions: In this series, neither single nor the association of US features are specific for MTC. The five main RSS correctly identify less than 50% of MTC and do not suggest performing FNAC in about half of them with potentially missed or delayed diagnosis.